Cellular effects of everolimus and sirolimus on podocytes - Müller-Krebs, Sandra; Weber, Lena; Tsobaneli, Julia; Kihm, Lars Philipp; Reiser, Jochen; Zeier, Martin; Schwenger, Vedat (PLOS ONE, 2013)
Everolimus (EVL) and Sirolimus (SRL) are potent immunosuppressant agents belonging to the group of mammalian target of rapamycin (mTOR) inhibitors used to prevent transplant rejection. However, some patients develop proteinuria following a switch from a calcineurin inhibitor regimen to mTOR inhibitors. Whether different mTOR inhibitors show similar effects on podocytes is still unknown. To analyze this, human podocytes were incubated with different doses of EVL and SRL. After incubation with EVL or SRL, podocytes revealed a reduced expression of total mTOR. Phosphorylation of p70S6K and Akt was diminished, whereas pAkt expression was more reduced in the SRL group. In both groups actin cytoskeletal reorganization was increased. Synaptopodin and podocin expression was reduced as well as nephrin protein, particularly in the SRL group. NFκB activation and IL-6 levels were lower in EVL and SRL, and even lower in SRL. Apoptosis was more increased in SRL than in the EVL group. Our data suggests that mTOR inhibitors affect podocyte integrity with respect to podocyte proteins, cytoskeleton, inflammation, and apoptosis. Our study is the first to analyze both mTOR inhibitors, EVL and SRL, in parallel in podocytes. Partially, the impact of EVL and SRL on podocytes differs. Nevertheless, it still remains unclear whether these differences are of relevance regarding to proteinuria in transplant patients.
Gesehen am 22.06.2021